Triglyceride-Glucose Index Predicts Major Adverse Cardiovascular and Cerebrovascular Events in Non-Diabetic Individuals - Li, Cangtuo; Qi, Qi; Li, Wansong; Zhang, Xuechao; Li, Lei; Deng, Jie; Han, Quanle; Wu, Shouling; Li, Kangbo (Balkan medical journal, 2025)
The association between the triglyceride-glucose (TyG) index and the occurrence of major adverse cardiovascular and cerebrovascular events (MACCEs) in individuals without diabetes has not been clearly established. To investigate the potential of the TyG index to predict MACCEs in a non-diabetic population. Prospective cohort study. This study analyzed data from 88,946 participants without diabetes, who were divided into four groups based on their TyG index values. The primary outcome was the occurrence of MACCEs, defined as myocardial infarction (MI) or stroke. Multivariable Cox proportional hazards regression models were used to assess the association between the TyG index and MACCEs. Participants in the higher TyG index quartiles exhibited a greater risk of MACCEs. Moreover, a significant interaction between the TyG index and sex was identified, with a stronger association observed in women than in men. A significant interaction was also found between the TyG index and age in relation to MI risk, indicating a stronger associations in individuals younger than 60 compared to those aged 60 or older. The TyG index may serve as a useful prognostic marker for MACCEs among individuals without diabetes.